Pemanfaatan Limbah Kotoran Ternak Sebagai Energi Alternatif Skala Rumah Tangga Di Desa Tegalweru - Listyawati, Ratih Novi; Meidiana, Christia; Anggraeni, Mustika (Fakultas Teknik, Universitas Brawijaya, 2013)
Tegalweru village is dominated by farmers, with the total number of cows are 1.080. But, the results of the primary survey show that only 27 cows ware utilized as biogas to produce an alternative energy source. In order to improve the utilization of manure waste into biogas there are 3 analysis used in this research, there are emergy analysis, IPA analysis and regression analysis. Emergy analysis was used to determine the best scenario to be applied in Tegalweru Village. Furthermore, IPA analysis was used to evaluate the performance of existing biogas and also regression analysis to find out the factors that influence the interest of farmers to use biogas. The results showed that the best scenario to be applied is the utilization of manure from 1,080 cows. Evaluation of the performance of biogas showed that the variables which have a high level of importance but low satisfaction levels are the availability of land for biogas, energy for cooking and energy for lighting. While some variables that significantly influence the farmers to have biogas installation are the availability of land, level of education and number of cows which they have. The output of the analysis are recommendations based on the analysis which had been done before. The recommendations for farmers as users of biogas derived from IPA analysis results and recommendations for non-biogas farmers derived from the results of the regression analysis.Keywords: Livestock Manure Waste, Emergy Analysis, Biogas.